Transfer of ochratoxin A from raw black tea to tea infusions prepared according to the Turkish tradition - Toman, Jakub; Malir, Frantisek; Ostry, Vladimir; Kilic, Mehmet Akif; Roubal, Tomas; Grosse, Yann; Pfohl-Leszkowicz, Annie (Journal of the science of food and agriculture, 2018)
BACKGROUND: Ochratoxin A (OTA) is a natural contaminant of food including tea with multiple toxic effects, which poses a threat to human health. In terms of lifestyle, the Turkish population is a frequent visitor of tearooms, and the traditional Turkish tea preparation is one of the most popular ways of preparing tea infusion. RESULTS: The aim of this study was to investigate OTA transfer from raw black tea to the tea infusion prepared according to the Turkish tradition. A high-performance liquid chromatography method with a limit of quantification of 0.35 ng g-1 was used for OTA determination. The OTA amount in raw black teas from Turkey ranged from ≤0.35 ng g-1 up to 56.7 ng g-1 . An homogenised sample of black tea naturally contaminated with 55.0 ng g-1 was used to prepare infusions. The OTA transfer from the black tea to the infusion was found to be 41.5% ± 7%. CONCLUSION: These data are important for the realisation of a 'Total Diet study' (TDS). The TDS can be a complementary tool to estimate the population dietary exposure to OTA across the entire diet by analysing main foods prepared 'as consumed' (tea infusions) and not 'as purchased' (raw tea). © 2017 Society of Chemical Industry.
Keywords: čaj; ochratoxin A; OTA; Turecko; Camellia sinensis; Turkey; Chromatography, High Pressure Liquid; transfer; Tea; vysokoúčinná kapalinová chromatografie; kontaminace potravin; Black tea; Humans; Food Contamination; infusion; HPLC-FLD; ochratoxiny; čajovník čínský; lidé; Ochratoxins